Kebijakan Pendidikan Pasca Pandemi Covid-19 di Madrasah Berbasis Pedesaan - Abdullah, Wawan; B. Syafuri; Anis Fauzi (AL MURABBI, 2024)
The COVID-19 pandemic has changed the way of learning and teaching worldwide, including Islamic education. Post-pandemic Islamic education innovation policies must consider these changes and strengthen schools' ability to provide quality education. One innovative policy that can be implemented is utilizing digital technology in madrasas. The obstacle faced, especially in rural areas, is infrastructure that is not yet optimal. The research method uses qualitative at Madrasah Tsanawiyah Mathlaul Anwar Lilnahdhatul Ulama (MALNU) Menes Pandeglang Regency with a case study approach. Data collection techniques using observation and literature study. The analysis technique uses descriptive. The research results show that madrasas have digital technology to support effective learning with interactive online learning applications, video tutorials, and platforms for discussion and collaboration between students and teachers. Islamic education innovation policies are strengthened through teachers' training and professional development in digital technology and teaching methods. Madrasas has provided support and training to teachers to acquire new online teaching skills and use digital technology effectively. The research implies that the better the policies with digital learning innovations after COVID-19, the more optimal the infrastructure will be in rural-based madrasas.